2014
DOI: 10.1007/s00709-014-0657-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of microbes for enhancing bacoside content and reduction of Meloidogyne incognita infestation in Bacopa monnieri L

Abstract: Despite the vast exploration of rhizospheric microbial wealth for crop yield enhancement, knowledge about the efficacy of microbial agents as biocontrol weapons against root-knot disease is scarce, especially in medicinal plants, viz., Bacopa monnieri. In the present investigation, rhizospheric microbes, viz., Bacillus megaterium, Glomus intraradices, Trichoderma harzianum ThU, and their combinations were evaluated for the management of Meloidogyne incognita (Kofoid and White) Chitwood and bacoside content enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…In the case of G. intraradices the inoculum was propagated on maize ( Zea mays ) roots for 10 weeks in a 1:1 (v/v) mixture of sterilized sand and soil (5 kg) with a low phosphorus content (7.5 kg ha −1 ) and subsequently left to shade‐dry for 2 weeks. The inoculum potential of G. intraradices used in the present experiment consisted of soil containing spores (8–10 spores g −1 ) with colonized roots of maize …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of G. intraradices the inoculum was propagated on maize ( Zea mays ) roots for 10 weeks in a 1:1 (v/v) mixture of sterilized sand and soil (5 kg) with a low phosphorus content (7.5 kg ha −1 ) and subsequently left to shade‐dry for 2 weeks. The inoculum potential of G. intraradices used in the present experiment consisted of soil containing spores (8–10 spores g −1 ) with colonized roots of maize …”
Section: Methodsmentioning
confidence: 99%
“…Therefore an efficient and ecofriendly alternative method for increased production is needed. In this context, the utilization of organic materials and bioinoculants to increase various crop yields is well documented . However, no specific study dealing with the effect of bioinoculants on the growth, essential oil components, total antioxidant content and glandular trichomes of P. graveolens has been done, especially in the context of synergistic application.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum increase in withaferin A by 4.00 fold was recorded in BS_CC followed by 3.00 fold in both STR_CF and TH_CC treatments as compared to the control plants (Table 1). Recently, a study showed that application of plant growth promoting microbes significantly enhanced secondary metabolite content in medicinal and aromatic plants like Bacopa monnieri, W. somnifera and Pelargonium graveolens (Rajasekar and Elango 2011;Gupta et al 2015bGupta et al , 2016. Increase in antioxidant capacity in TH_CF could also be positively correlated with increased Withanolide A, a well known antioxidant molecule.…”
Section: Resultsmentioning
confidence: 99%
“…MTN14 (KF699062) and T. harzianum ThU were individually maintained on Luria-Bertani (LB) agar, glucose yeast malt (GYM) agar, and potato dextrose agar (PDA) respectively at room temperature and subcultured monthly. The selection of cultures was done on the basis of their plant growth enhancing traits (Gupta et al 2015b;Gupta and Pandey 2015).…”
Section: Microbial Strains and Culture Conditionsmentioning
confidence: 99%
“…L effectively and even performed better than chemical nematicides as they colonize root and have direct interaction making impact on plant health and nematode management (Gupta et al, 2014).…”
Section: Discussionmentioning
confidence: 99%